2022
DOI: 10.3390/jof8070746
|View full text |Cite
|
Sign up to set email alerts
|

Organization and Unconventional Integration of the Mating-Type Loci in Morchella Species

Abstract: True morels (Morchella spp.) are a group of delicious fungi in high demand worldwide, and some species of morels have been successfully cultivated in recent years. To better understand the sexual reproductive mechanisms of these fungi, we characterized the structure of the mating-type loci from ten morel species, and seven of them were obtained using long-range PCR amplification. Among the studied species, eight were heterothallic, two were homothallic, and four types of composition were observed in the MAT lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…21110 and M04M24 of M. importuna, as reported by Liu et al [19], shared a similar configuration. Similarly, the MAT idiomorph of V. bohemica aligned with the structure of M. rufobrunnea, as published by Chai et al [21], where the MAT1-1-10, MAT1-1-1, and MAT1-2-1 genes were arranged in a tandem array. However, discernible structural disparities existed between the MAT loci of these two species.…”
Section: Structure Of Mating-type Loci Between Verpa Bohemica and Ver...supporting
confidence: 71%
See 2 more Smart Citations
“…21110 and M04M24 of M. importuna, as reported by Liu et al [19], shared a similar configuration. Similarly, the MAT idiomorph of V. bohemica aligned with the structure of M. rufobrunnea, as published by Chai et al [21], where the MAT1-1-10, MAT1-1-1, and MAT1-2-1 genes were arranged in a tandem array. However, discernible structural disparities existed between the MAT loci of these two species.…”
Section: Structure Of Mating-type Loci Between Verpa Bohemica and Ver...supporting
confidence: 71%
“…Incorporating the revelations derived from Morchella genus by Chai et al [21], motif analysis was employed to characterize the domains within the MAT1-1-10 and MAT1-1-11 proteins. Through MEME analysis, a total of 17 recognized protein motifs were unveiled within the MAT1-1-10 protein, while the MAT1-1-11 protein contained 10 conserved protein motifs.…”
Section: Analysis Of Conserved Motifs Of Mat1-1-10 and Mat1-1-11 Prot...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was preliminarily confirmed that nearly half of the phylogenetic species in the Morchella genus have a heterologous life cycle [ 27 , 33 , 50 , 51 ]. At the same time, it has been demonstrated that there are some morel species that have a homothallic life cycle [ 38 , 52 ]. In order to systematically explore the monosporal homokaryotic and heterothallic life cycle traits of M. importuna , we have sequenced, assembled, and compared the genomes of two monosporic strains with different mating type gene structures of M. importuna .…”
Section: Relevance On Biological Research For Steady Cultivation Indu...mentioning
confidence: 99%
“…Morchella spp. are considered to primarily be heterothallic, but secondary homothallism (Du and Yang 2021 ) and primary homothallism (Chai et al 2022 ) have also been observed. Furthermore, the mating strategies can be mixed within a single species.…”
Section: Introductionmentioning
confidence: 99%